Can niche plasticity promote biodiversity–productivity relationships through increased complementarity?. Issue 4 (20th March 2017) - Niklaus, Pascal A.; Baruffol, Martin; He, Jin‐Sheng; Ma, Keping; Schmid, Bernhard
Abstract: Most experimental biodiversity–ecosystem functioning research to date has addressed herbaceous plant communities. Comparably little is known about how forest communities will respond to species losses, despite their importance for global biogeochemical cycling. We studied tree species interactions in experimental subtropical tree communities with 33 distinct tree species mixtures and one, two, or four species. Plots were either exposed to natural light levels or shaded. Trees grew rapidly and were intensely competing above ground after 1.5 growing seasons when plots were thinned and the vertical distribution of leaves and wood determined by separating the biomass of harvested trees into 50 cm height increments. Our aim was to analyze effects of species richness in relation to the vertical allocation of leaf biomass and wood, with an emphasis on bipartite competitive interactions among species. Aboveground productivity increased with species richness. The community‐level vertical leaf and wood distribution depended on the species composition of communities. Mean height and breadth of species‐level vertical leaf and wood distributions did not change with species richness. However, the extra biomass produced by mixtures compared to monocultures of the component species increased when vertical leaf distributions of monocultures were more different. Decomposition of biodiversity effects with the additive partitioning scheme indicated positive complementarity effects that were higher in light than in shade. Selection effects did not deviate from zero, irrespective of light levels. Vertical leaf distributions shifted apart in mixed stands as consequence of competition‐driven phenotypic plasticity, promoting realized complementarity. Structural equation models showed that this effect was larger for species that differed more in growth strategies that were characterized by functional traits. In 13 of the 18 investigated two‐species mixtures, both species benefitted relative to intraspecific competition in monoculture. In the remaining five pairwise mixtures, the relative yield gain of one species exceeded the relative yield loss of the other species, resulting in a relative yield total (RYT) exceeding 1. Overall, our analysis indicates that richness–productivity relationships are promoted by interspecific niche complementarity at early stages of stand development, and that this effect is enhanced by architectural plasticity.